Association between age at disease onset of anti-neutrophil cytoplasmic antibody-associated vasculitis and clinical presentation and short-term outcomes - DİRESKENELİ, RAFİ HANER (My University, 2021)
Objectives. ANCA-associated vasculitis (AAV) can affect all age groups. We aimed to show that differences in disease presentation and 6 month outcome between younger- and older-onset patients are still incompletely understood. Methods. We included patients enrolled in the Diagnostic and Classification Criteria for Primary Systemic Vasculitis (DCVAS) study between October 2010 and January 2017 with a diagnosis of AAV. We divided the population according to age at diagnosis: <65 years or 65 years. We adjusted associations for the type of AAV and the type of ANCA (anti-MPO, anti-PR3 or negative). Results. A total of 1338 patients with AAV were included: 66% had disease onset at <65 years of age [female 50%; mean age 48.4 years (S.D. 12.6)] and 34% had disease onset at 65 years [female 54%; mean age 73.6 years (S.D. 6)]. ANCA (MPO) positivity was more frequent in the older group (48% vs 27%; P ¼ 0.001). Younger patients had higher rates of musculoskeletal, cutaneous and ENT manifestations compared with older patients. Systemic, neurologic,cardiovascular involvement and worsening renal function were more frequent in the older-onset group. Damage accrual, measured with the Vasculitis Damage Index (VDI), was significantly higher in older patients, 12% of whom had a 6 month VDI 5, compared with 7% of younger patients (P ¼ 0.01). Older age was an independent risk factor for early death within 6 months from diagnosis [hazard ratio 2.06 (95% CI 1.07, 3.97); P ¼ 0.03]. Conclusion. Within 6 months of diagnosis of AAV, patients >65 years of age display a different pattern of organ involvement and an increased risk of significant damage and mortality compared with younger patients.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; ROMATOLOJİ; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; RHEUMATOLOGY; PHARMACOLOGY & PHARMACY; Romatoloji; Farmakoloji (tıbbi); Rheumatology; Pharmacology (medical); age; anti-neutrophil cytoplasmic antibody-associated vasculitis; outcome; nti-neutrophil cytoplasmic antibody–associated vasculitis; age; outcome